Citation Analysis in Health Care Sciences - Rigby, M. (Methods of Information in Medicine, 2014)
Background: Citations of scientific papers in health care have become a subject of interest, as in any scientific sector. However, such a metric, while useful in a simple way, can become subject to too much credibility, and therefore to advanced analyses which are not soundly grounded even if methodologically valid.Objectives: The objective was to contextual-ise citation indices in health care science, juxtaposed with a parallel analytic paper.Methods: The literature was reviewed and set against the objectives of metrics of literature and of researchers.Results: The strengths and weaknesses of citation indices in the health sector were identified, with practical examples of perverse effects, and compared with the core objectives of health care development.Conclusions: Citation indices in health care science have a value, but this is limited to giving a broad overview. Other measures of effectiveness, including impact on education, on health care development, and on stimulation of applied developments, are needed rather than spuriously scientific advanced analyses of citation counts.
Keywords: Citation index; bibliometrics; quality of papers; quality of research; health care improvement; measurement